Genetic toolkits of the red alga Pyropia tenera against the three most common diseases in Pyropia farms. Issue 4 (22nd May 2019) - Im, Soo Hyun; Klochkova, Tatyana A.; Lee, Da Jeoung; Gachon, Claire M. M.; Kim, Gwang Hoon
Abstract : Disease outbreaks devastate Pyropia aquaculture farms every year. The three most common and serious diseases are Olpidiopsis‐ blight and red‐rot disease caused by oomycete pathogens and green‐spot disease caused by the PyroV1 virus. We hypothesized that a basic genetic profile of molecular defenses will be revealed by comparing and analyzing the genetic response of Pyropia tenera against the above three pathogens. RNAs isolated from infected thalli were hybridized onto an oligochip containing 15, 115 primers designed from P. tenera expressed sequence tags (EST)s. Microarray profiles of the three diseases were compared and interpreted together with histochemical observation. Massive amounts of reactive oxygen species accumulated in P. tenera cells exposed to oomycete pathogens. Heat shock genes and serine proteases were the most highly up‐regulated genes in all infection experiments. Genes involved in RNA metabolism, ribosomal proteins and antioxidant metabolism were also highly up‐regulated. Genetic profiles of P. tenera in response to pathogens were most similar between the two biotrophic pathogens, Olpidiopsis pyropiae and PyroV1 virus. A group of plant resistance genes were specifically regulated against each pathogen. Our results suggested that disease response in P. tenera consists of a general constitutive defense and a genetic toolkit against specific pathogens.